Improving Student Learning Outcomes through Problem-Based Learning (PBL) Model in Science Subjects of Class VIII-1 and VIII-2 at SMP Negeri 2 Mesjid Raya Aceh Besar: A Literature Study - FITRIA AGUSTINA AGUS (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to analyze the influence of the Problem-Based Learning (PBL) method on improving student learning outcomes in the subject of Natural Sciences (IPA) in classes VIII-1 and VIII-2 at SMP Negeri 2 Mesjid Raya Aceh Besar. Problem-Based Learning is an engaging alternative in the context of education because it creates a more interactive and contextual learning environment. In this study, we examine various literature and academic sources discussing the implementation of PBL in education, focusing on how this model can enhance student engagement, conceptual understanding, and critical and creative thinking skills. The PBL method encourages students to solve problems relevant to the real world, allowing them to connect theory with practice. Through this literature study, we have collected and analyzed data from various studies demonstrating that implementing PBL positively impacts student motivation and academic performance. The results of this analysis indicate that students engaged in problem-based learning show significant improvement in their understanding of basic IPA concepts and problem-solving abilities. Thus, this research concludes that the application of the PBL model is not only effective in enhancing student learning outcomes in junior high schools but also contributes to the development of character and 21st-century skills that are essential for students. This study is expected to provide recommendations for educators and educational institutions to consider the implementation of problem-based learning models in classroom instruction.